Determinação dos tipos de resistência de genótipos de feijoeiro ao ataque de Zabrotes subfasciatus (Boh.) (Coleoptera: Bruchidae) - Mazzonetto, Fábio [UNESP]; Boiça Jr, Arlindo L. [UNESP] (Sociedade Entomológica do Brasil, 1999)
With the purpose of looking for alternative means for the control of Zabrotes subfasciatus (Boheman) (Coleoptera: Bruchidae), that work had for objetive, to determine the resistance types involved in bean genotypes to its attack. It was realized no choice and free choice tests and the treatments were arranged in a completely randomized design with four and five replications, respectively, with samples of 10g of seeds. In no choice test was sampled the parameters total number of eggs, number of viable eggs, viability of eggs, dry wieght of the consumed food, biological cycle of egg to adult, number and percentage of emerged insects and weigth and longevity of females and males. For the free choice test, was evaluated the number of insects attract for the genotypes, total number of eggs and number of egg for female. With the obtained results, it can be concluded that the genotypes Preto 143 present resistance of the type nonpreference for oviposition in test free choice; and, the genotypes 2374, 2395, 2174, 133 and 155, present resistance of the type nonpreference for feeding and/or antibiosis.

Com a finalidade de buscar meios alternativos para o controle de Zabrotes subfasciatus (Boheman) (Coleoptera: Bruchidae), este trabalho teve por objetivo, determinar os tipos de resistência envolvidos em genótipos de feijoeiro ao seu ataque. Foram realizados testes sem e com chance de escolha utilizando o delineamento estatístico inteiramente casualizados, com quatro e cinco repetições, respectivamente, com amostras de 10g de grãos. Em teste sem chance de escolha foram amostrados os parâmetros número total de ovos, número de ovos viáveis, viabilidade de ovos, peso seco do alimento consumido, ciclo biológico de ovo a adulto, número e porcentagem de insetos emergidos, e peso e longevidade de fêmeas e machos. Para o teste com chance de escolha, avaliou-se o número de insetos atraídos pelos genótipos, número total de ovos e número de ovos por fêmea. Com os resultados obtidos, pode-se concluir que o genótipo Preto 143 apresenta resistência do tipo não-preferência para oviposição em teste com chance de escolha; e, os genótipos 2374, 2395, 2174, 133 e 155, apresentaram resistência do tipo não-preferência para alimentação e/ou antibiose.
Determination of the types of resistance of bean genotypes to the attack of Zabrotes subfasciatus (Boh.) (Coleoptera: Bruchidae)
Keywords: Insecta; host plant resistance; stored bean; Insecta; resistência de plantas; grãos armazenados